2016
DOI: 10.4102/ojvr.v83i1.1045
|View full text |Cite
|
Sign up to set email alerts
|

An acetone extract of <i>Clausena</i> <i>anisata</i> may be a potential control agent for flies encountered in cutaneous myiasis

Abstract: Clausena anisata is a medicinal plant used traditionally to treat myiasis and as an insect repellent by various communities. We have previously demonstrated the effects of C. anisata extracts on blowfly feeding and development in our laboratory. The impact of C. anisata leaf extracts on populations of different fly species on farms in Mpumalanga, South Africa was investigated in this study under field conditions. Flies were exposed to liver baits treated with acetone leaf extracts of C. anisata (150 mg/mL). Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Clausena anisata (horsewood) is a medicinal plant used as a maggot‐expelling agent to treat myiasis (Chavunduka 1976). An acetone extract of C. anisata repelled the blow flies from the baits (Mukandiwa et al 2016). In test situations , Lucilia cuprina laid only very few egg masses on fleece to which 0.5% of the repellent 1,1‐Bis(4‐ethoxyphenyl)‐2‐nitropropane (GH74) had been applied, and which had been exposed in the field for up to six months.…”
Section: Discussionmentioning
confidence: 99%
“…Clausena anisata (horsewood) is a medicinal plant used as a maggot‐expelling agent to treat myiasis (Chavunduka 1976). An acetone extract of C. anisata repelled the blow flies from the baits (Mukandiwa et al 2016). In test situations , Lucilia cuprina laid only very few egg masses on fleece to which 0.5% of the repellent 1,1‐Bis(4‐ethoxyphenyl)‐2‐nitropropane (GH74) had been applied, and which had been exposed in the field for up to six months.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of C. anisata on the behaviour and development of blowfly larvae have been investigated (Mukandiwa et al, 2012a, b;2016a). In both laboratory and field studies, where fly larvae were exposed to meat or liver baited with the acetone leaf extracts (10mg/ml -150mg/ml).…”
Section: Activity Against Blowfliesmentioning
confidence: 99%
“…Ivermectin was used as a positive control while acetone and water served as solvent controls. Developmental anomalies in the larvae, which included paralysis, prolongation of the larval stage, reduced pupation rates and pupae malformations (Mukandiwa et al, 2012a, b;2016a) were reported. The authors have suggested that these effects indicate that the plant extracts interfere with neuroendocrine control of movement and moulting in the blowfly (Mukandiwa et al, 2012a, b).This may be due to the presence of coumarins and alkaloids within the plant species (as discussed earlier) which are known to inactivate the acetylcholinesterase enzyme (AChE) (Aniszewski, 2007;Khanikor et al, 2013).…”
Section: Activity Against Blowfliesmentioning
confidence: 99%
“…is a herbal medicinal plant belonging to the Rutaceae or Citrus family. It has been investigated for several activities including analgesic [1], antidiabetic [2,3], anti-inflammatory [4,5], antimalarial [1], antimicrobial [3,[6][7][8][9], antioxidant [3,10,11], antipyretic [4], cytotoxic [6], larvicidal [12][13][14][15][16], smoking cessation aid [17], and wound healing [11] effects. The five major compounds containing in essential oils of C. anisata leaves growing in North-Central Nigeria are anethole (31.3%), trans-β-ocimene (20.0%), caryophyllene (10.5%), estragole (6.9%), and α-pinene (6.7%) [18].…”
Section: Introductionmentioning
confidence: 99%